A simulation study of the influence of the traveling wave patterns on ion mobility separations in structures for lossless ion manipulations. Issue 1 (20th November 2019) - Li, Ailin; Garimella, Sandilya V. B.; Ibrahim, Yehia M.
Abstract : Probing molecular properties in the gas phase requires the integration of complementary ion manipulation approaches such as ion mobility spectrometry. Abstract : Probing molecular properties in the gas phase requires the integration of complementary ion manipulation approaches such as ion mobility spectrometry. Structures for lossless ion manipulations (SLIM) have recently been developed to perform ultra-high resolution ion mobility separations using traveling waves as well as providing other advanced capabilities. Despite its success, the design aspects of SLIM have not been fully explored and remained largely unchanged. Here, we report on a computational study using SIMION simulations of a number of traveling wave (TW) patterns that can be used in SLIM. The TW pattern used in the current SLIM device is a set of 8 electrodes where, at any time, 4 electrodes are held at high voltage ( i.e., 1111), while the other 4 electrodes are held at low voltage ( i.e., 0000), forming one micro-trapping region of 11110000 pattern. Ion trajectory simulations demonstrated the feasibility to simplify the 8-electrode set to a shorter pattern ( e.g., 6-electrode or 4-electrode set) while maintaining or improving the performance. The RF and TW amplitudes, guard voltage, and TW speed were optimized subsequently on the symmetric patterns of the 4-, 6-, and 8-electrode sets to further improve the performance. The resolution, peak broadening, peak capacity, and peak generation rate of each pattern were evaluated, showing that the 111000 pattern of the 6-electrode set has comparable performance to the current 11110000 pattern and is always better than the 1100 pattern. This work provides insight into the feasibility for simplification and modification of the TW configuration in SLIM and other traveling wave devices.